2017
DOI: 10.1002/cbdv.201600268
|View full text |Cite
|
Sign up to set email alerts
|

First Report on Rare Unifloral Honey of Endemic Moltkia petraea (Tratt.) Griseb. from Croatia: Detailed Chemical Screening and Antioxidant Capacity

Abstract: Rare Moltkia petraea (Tratt.) Griseb. honey from Croatia was first time characterised. The spectrophotometric assays on CIE L*a*b*C *h ° colour coordinates, total phenol content and antioxidant capacity (FRAP, CUPRAC, DPPH and ABTS assays) determined higher honey values generally close to dark honeys ranges. Headspace solid-phase microextraction (HS-SPME) on two fibres after GC-FID and GC/MS revealed the major compounds 2-phenylacetaldehyde (12.8%; 15.6%), benzaldehyde (11.1%; 10.0%), octane (9.3%; 7.6%), nona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Our results showed that all honey extracts exhibited significant antioxidant activity that may be related with their phenolic and flavonoid content. This finding is in accordance with previous studies demonstrating the antioxidant properties of honey extracts [51][52][53][54][55][56][57]. Interestingly, a strong correlation between the TPC and the antioxidant capacity of honey has been reported by a great number of studies [58][59][60].…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that all honey extracts exhibited significant antioxidant activity that may be related with their phenolic and flavonoid content. This finding is in accordance with previous studies demonstrating the antioxidant properties of honey extracts [51][52][53][54][55][56][57]. Interestingly, a strong correlation between the TPC and the antioxidant capacity of honey has been reported by a great number of studies [58][59][60].…”
Section: Discussionsupporting
confidence: 93%
“…The headspace solid‐phase microextraction was performed by manual sampler (Supelco) using the fiber polydimethylsiloxane/carboxene/divinylbenzene (PDMS/CARB/DVB) as described in the previous articles. [ ][ ] The extraction time was 45 min, and the sample was equilibrated at 60 °C for 15 min. The extraction was performed in triplicate and each replicate was analyzed by gas chromatography and mass spectrometry (GC/MS).…”
Section: Methodsmentioning
confidence: 99%
“…The S. montana honey had a DPPH radical-inhibition activity of 0.5-1.0 mmol TEAC/kg and a ferric-reducing antioxidant activity between 2.5 and 5.1 mmol Fe 2+ /kg. The chemical profile, analyzed by HPLC-DAD, revealed the presence of syringic acid (0.10-1.70 mg/kg) (Jerković et al, 2015). This compound has antidiabetic activity in experimental models of mice with diabetes (Muthukumaran et al, 2013).…”
Section: Biological Activity Of Monofloral Honeysmentioning
confidence: 98%
“…Another monofloral honey from Croatia, derived from Moltkia petraea from the Biokovo mountains, was analyzed for its antioxidant activity (FRAP, DPPH, and ABTS) (Jerković et al., 2017). The results showed a moderate antioxidant activity by means of the FRAP test.…”
Section: Biological Activity Of Monofloral Honeysmentioning
confidence: 99%